Experimental study on axial compression performance of I-shaped aluminum concrete columns embedded in CFRP-PVC square tubes - Yuhua Wang; Mengjun Wang; Congrong Tang; Yong Yu; Jiaju Pang (PLoS ONE, 2025)
To investigate the axial compressive behavior of CFRP-PVC square tube-embedded aluminum concrete columns, five specimens and one control specimen without I-shaped aluminum were tested under uniaxial compression, with the number of CFRP layers and spacing as variable parameters. The failure modes, load-displacement responses, and mechanical properties such as peak load, ductility, stiffness, and energy dissipation were systematically analyzed. Results showed that the incorporation of I-shaped aluminum improved the peak load and ductility by an average of 48.4% and 6.2%, respectively. Increasing the number of CFRP layers increased the bearing capacity by 62.6% for one layer and 69.8% for two layers. Ductility decreased by approximately 15.4% with one layer due to limited confinement but improved by about 15.3% with two layers as the enhanced restraint mitigated stress concentrations and strengthened the composite action. Enlarging the CFRP spacing reduced the bearing capacity by an average of 7.4% but had negligible effect on ductility. The addition of I-shaped aluminum enhanced the axial stiffness by an average of 6.2%, and increasing CFRP layers effectively mitigated stiffness degradation. All specimens exhibited CFRP-PVC or PVC tube rupture and I-shaped aluminum flange buckling, with buckling locations shifting upward as confinement increased. A validated ABAQUS model was used to explore the composite confinement mechanism, and a new confinement model was proposed. The proposed composite columns offer enhanced mechanical performance and durability, making them promising candidates for practical applications in lightweight and high-performance structural elements.